2013
DOI: 10.4013/base.2013.104.03
|View full text |Cite
|
Sign up to set email alerts
|

A visão da honestidade acadêmica de professores e alunos de um curso superior em Contabilidade

Abstract: RESUMOPes quisas indicam que o comportamento ético dos alunos de graduação tem impacto na vida profissional do futuro contador. Respondendo às demandas internacionais para maiores reflexões sobre a ética profissional e acadêmica, esta pesquisa procura, nos cursos superiores contábeis, subsídios nas visões de alunos e professores em relação à honestidade acadêmica para fomentar a discussão. Inexistem pesquisas no Brasil que comparam as percepções de professores e alunos no ensino de graduação contábil em relaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 26 publications
3
9
1
3
Order By: Relevance
“…Regarding the undergraduate course in accounting, two similar studies to this one were found concerning the aim of evaluating the perception of teachers and students with respect to academic dishonesty: that of Oliveira and Chacarolli (2013) and that of Oliveira et al (2014). As in previous papers, the studies indicate differences in perceptions in gray cases alone; that is, those that are hard to identify as honest or dishonest.…”
Section: Previous Studies and Research Hypothesessupporting
confidence: 53%
See 3 more Smart Citations
“…Regarding the undergraduate course in accounting, two similar studies to this one were found concerning the aim of evaluating the perception of teachers and students with respect to academic dishonesty: that of Oliveira and Chacarolli (2013) and that of Oliveira et al (2014). As in previous papers, the studies indicate differences in perceptions in gray cases alone; that is, those that are hard to identify as honest or dishonest.…”
Section: Previous Studies and Research Hypothesessupporting
confidence: 53%
“…Internationally, the studies on academic dishonesty have been developed in undergraduate courses in the areas of business, including accounting (Braun & Stallworth, 2009;Bujaki et al, 2019;Johns & Strand, 2000;Kisamore et al, 2007), chemistry (Simon et al, 2004), and others (Lambert et al, 2003). In Brazil, studies on the theme are found in undergraduate courses in the areas of law, management, pedagogy, engineering (Pimenta, 2010), health (Sousa et al, 2016), accounting, and business (Avelino & Lima, 2017;Oliveira & Chacarolli, 2013;Oliveira et al, 2014;Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Internacionalmente, os estudos sobre desonestidade acadêmica foram desenvolvidos em cursos de graduação nas áreas de: Negócios (BRAUN; STALLWORTH, 2009; JOHNS; STRAND, 2000;KISAMORE;STONE;JAWAHAR, 2007); Química (SIMON et al, 2004); diversas (LAMBERT;HOGAN;BARTON, 2003). No Brasil, são encontrados estudos do tema em cursos de graduação nas áreas de: Direito, Administração, Pedagogia e Engenharia (PIMENTA, 2010); Ciências Contábeis e Negócios (OLIVEIRA et al, 2014;OLIVEIRA NETO;CHACAROLLI JÚNIOR, 2013) e na área de saúde (SOUSA et al, 2016).…”
Section: Introductionunclassified